TERMINOLOGIYADA OMONIMLIK VA POLISEMIYA MUNOSABATI (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the relationship and distinctions between homonymy and polysemy within the terminology system of the Uzbek language. Polysemy is defined as the presence of multiple related meanings within a single lexical unit, whereas homonymy is characterized by identical forms assigned to completely independent meanings. The study highlights the importance of accurately differentiating these phenomena in scientific and technical communication, where each term must convey one clearly defined concept. The analysis employs semantic, etymological, systemic, and contextual criteria. Practical implications for translation studies, lexicography, and digital linguistic technologies are discussed. The findings underline the need for proper terminology standardization to ensure clarity and efficiency in interdisciplinary scientific discourse.